Efeitos dos parâmetros da extração e avaliação da qualidade física e química dos óleos de baru e amendoim - LIMA, Jean Carlos Rodrigues (2012)
This work aimed to optimize the extraction of baru oil (Dipteryx alata Vog.) by continuous mechanical pressing and assess its quality compared to peanut oil extracted under the same conditions, since both have similar characteristics. The characterization of fruit and baru almonds from southern state of Goiás was carried out, determining their chemical composition. Response surface methodology was used to assess the influence of process variables on the extraction yield and quality of oils. Analyses of moisture content, color, relative density, viscosity, refractive index, iodine value, saponification index, acidity, peroxide index, p-anisidine index and total oxidation value were conducted to assess the quality of the oils extracted. There was great variability in the physical characteristics of fruits and baru almonds, with almond yield in relation to fruits similar to literature (4.54%). Baru almond has composition similar to peanuts, with high energy density (594.43 kcal / 595.42 kcal) and nutrients, especially protein (23.66 g.100g-1 / 32.93 g.100g-1) and lipids (37.19 g.100g-1 / 46.14 g.100g-1). The efficiency of the extraction process was similar between baru (80.85%) and peanuts (81.08%) The process of baru oil extraction has been optimized with regard to yield and parameters tested. In evaluating the effect of the extraction parameters, there was positive contribution from the extraction temperature for baru, showing higher yield at maximum temperature and intermediate screw speed and negative effect of screw speed for peanuts, with higher performance in lower screw speeds, regardless of extraction temperature (p < 0.10). The baru oil color was slightly green (-1.41) and intense yellow color (73.97); peanut oil showed slightly green (-2.49) and slightly yellow color (13.42). There was little influence of extraction parameters on the quality of the oils studied, confirmed by the total oxidation value that combine results of peroxide index and p-anisidine values, indicating process stability.